1989
DOI: 10.1083/jcb.109.6.2833
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a direct, nucleotide-sensitive interaction between actin and liver cell membranes.

Abstract: Abstract. We have investigated the association of actin with membranes isolated from rat liver. A plasma membrane-enriched fraction prepared by homogenization in a low salt/CaCl2 buffer was found to contain a substantial amount of residual actin which could be removed by treatment with 1 M Na2CO3/NaHCO3, pH 10.5. Using a sedimentation binding assay that uses gelsolin to shorten actin filaments and render membrane binding saturable (Schwartz, M. A., and E. J. Luna. 1986. J. Cell Biol. 102:2067-2075, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…It was postulated by these investigators that such direct interactions between actin and cell membranes occur in vivo. Similar observations have also been made by several other groups (Gert de Couet et al, 1984;Tranter et al, 1989;Gillard et al, 1992). Therefore, in light of the above data, it is conceivable that actin is also present on many cell surfaces despite the absence of an actin signal peptide or a transmembrane domain.…”
Section: Discussionsupporting
confidence: 90%
“…It was postulated by these investigators that such direct interactions between actin and cell membranes occur in vivo. Similar observations have also been made by several other groups (Gert de Couet et al, 1984;Tranter et al, 1989;Gillard et al, 1992). Therefore, in light of the above data, it is conceivable that actin is also present on many cell surfaces despite the absence of an actin signal peptide or a transmembrane domain.…”
Section: Discussionsupporting
confidence: 90%
“…We recently reported that direct interactions between actin and integral membrane proteins also occur in the mammalian liver (Tranter et al, 1989). Using the sedimentationbinding assay mentioned above, we found that t2~I-actin binds specifically and saturably to liver cell membranes and that integral membrane proteins appear to be responsible.…”
mentioning
confidence: 85%
“…While electron micrographs show occasional filamentous structures attached to unstfipped liver cell membranes (Tranter et al, 1989), these filaments do not appear to be present in sufficient abundance to account for the level of endogenous membrane-bound actin (,o5 % of the total membrane protein). In addition, endogenous actin is very resistant to extraction by a variety of agents known to depolymerize actin filaments (Tranter et al, 1989;Hubbard and Ma, 1983). Interestingly, Hubbard and Ma (1983) have reported that actin bound to liver cell membranes does not bind myosin S-1.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to being a major protein of the contractile apparatus in muscle cells, actin is an important constituent of a diverse range of cellular processes including maintenance of the cytoskeleton, cytokinesis, and whole cell motility [Schwartz and Stone, 19831. Recent studies have indicated that actin may also play a role in gene transcription 0 1993 Wiley-Liss, Inc. and chromosome morphology [Ankenbauer et al, 19891, selective mRNA translation [Cheng and Bjerknes, 1989;Sundell and Singer, 19901, cellular localization and modulation of certain enzymes [Morita et al, 1989;Hunt et al, 1990;Farwell et al, 19901, and cytoskeletal interactions with the cell membrane [Tranter et al, 1989;St-Onge and Gicquaud, 19901. The classic studies of Vandekerckhove and coworkers [ Vandekerckhove and Weber, 1978,;1979a;1979b;Gabbiani et al, 19811 first established the presence of multiple distinct actin isotypes in vertebrates.…”
Section: Introductionmentioning
confidence: 99%